2019
DOI: 10.1371/journal.pone.0224903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Minimum Inhibitory Concentrations for 154 Mycoplasma synoviae isolates from Italy collected during 2012-2017

Abstract: Mycoplasma synoviae (MS) is a highly prevalent bacterial species in poultry causing disease and severe economic losses. Antibiotic treatment is one of the control strategies that can be applied to contain clinical outbreaks in MS-free flocks, especially because this bacterium can be transmitted in ovo. It becomes, then, very important for veterinarians to know the antibiotic susceptibility of the circulating strains in order to choose the most appropriate first-line antibiotic molecule as a proactive role in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…Ordinal regression methods using MIC as an outcome are rare in the literature. The usefulness of the proportional odds cumulative logit model is primarily limited to analysis of suspected progressive drift in MICs, an example of which can be found in Catania et al [56]. In this study, the proportional odds cumulative logit model was used to test for temporal trends in tilmicosin MIC, which were hypothesized to exhibit gradual increase towards resistance (i.e., MIC creep).…”
Section: Applications Of Regression Approaches For Ordinal Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Ordinal regression methods using MIC as an outcome are rare in the literature. The usefulness of the proportional odds cumulative logit model is primarily limited to analysis of suspected progressive drift in MICs, an example of which can be found in Catania et al [56]. In this study, the proportional odds cumulative logit model was used to test for temporal trends in tilmicosin MIC, which were hypothesized to exhibit gradual increase towards resistance (i.e., MIC creep).…”
Section: Applications Of Regression Approaches For Ordinal Datamentioning
confidence: 99%
“…In this study, the proportional odds cumulative logit model was used to test for temporal trends in tilmicosin MIC, which were hypothesized to exhibit gradual increase towards resistance (i.e., MIC creep). The model included the covariates "year" and the genotype of the Mycoplasma synoviae isolate, along with an interaction term [56]. Similarly, a second application of the proportional odds cumulative logit model can be found in Bote et al [57] which examines two narrow distributions of primarily susceptible MICs from E. coli isolates challenged with glyphosate isopropylamine salt and glyphosate-containing formulation.…”
Section: Applications Of Regression Approaches For Ordinal Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent years, several studies found high MIC values of macrolides and lincosamides against M . synoviae isolates [ 11 13 ]. Susceptibility of M .…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility of M . synoviae isolates to fluoroquinolones also decreased over the last few decades, which is particularly troublesome as the use of fluoroquinolones is critical in the therapy of humans as well [ 7 , 8 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%